Systemic Resilience Through the Integration of Leading and Lagging Indicators in Risk Management - Chaudhary, Kartik (Journal of Global Economy, Business and Finance, 2026)
This research explores the role of leading and lagging indicators in risk management and system resilience. By analyzing various predictive models and statistical methods, the study evaluates how integrating both types of indicators enhances risk forecasting and improves decision - making processes. The findings suggest that while leading indicators offer early warnings, lagging indicators provide essential feedback for refining strategies. The study concludes that a balanced integration of these indicators strengthens system resilience and reduces the adverse effects of uncertainties.